2020
DOI: 10.1002/npr2.12138
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self‐reporting depression in the Tabari cohort study population

Abstract: The World Health Organization (WHO) has identified depression as the fourth reason of disability in the world, accounting for the greater portion of nonlethal diseases, and predicts it to be the second cause of death by 2020 1-3. In a review study, the prevalence of lifetime depression varied from 1.5 percent in Taiwan to 19 percent in Lebanon. The average in western Germany was 9.2 percent, and in Edmonton in Canada, it was reported at 9.6 percent 1. An international research by the WHO, reported the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Zhu J et al found that the prevalence of anxiety and depression symptoms was 11.4% and 45.6% in physicians and 27.9% and 43.0% in nurses 35 . In a study in Singapore and India, the depression symptoms were reported 10.6% and anxiety symptoms were reported 15.7% in medical workers 36 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zhu J et al found that the prevalence of anxiety and depression symptoms was 11.4% and 45.6% in physicians and 27.9% and 43.0% in nurses 35 . In a study in Singapore and India, the depression symptoms were reported 10.6% and anxiety symptoms were reported 15.7% in medical workers 36 …”
Section: Discussionmentioning
confidence: 97%
“…In the current study, 51.4% and 52% of the nurses and doctors had depression symptoms, while 68.6% and 68.5% had anxiety symptoms. The nurses and doctors in Iran have experienced higher symptoms of anxiety and depression than in the China 35 and other countries 36 during the outbreak. Perhaps, one of the reasons is the lack of sufficient personal protective equipment such as gloves and masks at the beginning of the outbreak.…”
Section: Discussionmentioning
confidence: 98%
“…W.B.C count, O2 saturation, and ALP were related to lung involvement significantly. Cough, fever, and dyspnea were main symptoms (Zarghami et al, 2020). Abnormal HRCT was a main indicator to evaluate the COVID-19 disease.…”
Section: Resultsmentioning
confidence: 99%
“…The infection spread across other countries round the world (Zhu et al). On January 30, 2020, the World Health Organization (WHO) stated the outbreak a Public Health Emergency of International Concern (Sohrabi et al, 2020).the symptoms of COVID-19 can be fever, dry cough, fatigue, shortness of breath, myalgia or even no symptoms (Diao et al, 2020, Wan et al, 2020, Zarghami et al, 2020.likewise, the studies revealed that older age, male gender, leukocytosis, and Blood laboratory findings, also, comorbidities such as high lactate dehydrogenase level, cardiac injury, hypertension, diabetes mellitus, hypothyroidism, coronary artery disease, smoking and hyperglycemia, were related to weak prognosis in COVID-19 patients (Zhang et al, 2020b, Zarghami et al, 2019.Though, information concerning to clinical features of COVID-19 is still making it difficult for physicians to distinguish the causative agents without related laboratory analysis (Wu and McGoogan, 2020).Furthermore, reverse transcriptionpolymerase chain reaction (RT-), the gold standard for confirming diagnosis of COVID-19, has some restrictions, such as false negative results and limited sampling method and the rate of high false negative and unavailability of in the early stage of the outbreak restricted fast diagnosis of infection in patients (Fang et al, 2020). The high resolution computed tomography (HRCT) of the chest is progressively recognized as a strong indicator for early diagnosis, and can be the key to the evaluation of COVID-19 suspected patients because the changes in chest imaging sometimes maybe earlier than symptoms (He et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we also used self-reported measures of depression, anxiety and HIV status which are associated with high risk of social desirability bias. These forms of self-report may be more sensitive to identifying non-depressed, non-anxious and HIV negative individuals [36] because of the stigma associated with positive HIV and poor mental health status in sub-Saharan Africa [37][38][39][40]. Stigma may have resulted in under-reporting and an underestimation of the proportion of respondents who were depressed, anxious or PLHIV.…”
Section: Discussionmentioning
confidence: 99%